Health-related quality of life in patients with recurrent pericarditis: results from RHAPSODY, a phase 3 study of rilonacept. (14th October 2021) - Brucato, A; Lim-Watson, M Z; Imazio, M; Klein, A; Andreis, A; Andreis, A; Cella, D; Cremer, P; Lewinter, M; Luis, S A; Lin, D; Lotan, D; et al.
Abstract: Background: Recurrent pericarditis (RP) patients report that painful, debilitating flares negatively impact their health-related quality of life (HRQoL). RHAPSODY, the Phase 3 trial of rilonacept (IL-1α/IL-1β cytokine trap), included a daily pain diary and patient-reported outcome SF-36v2 to measure HRQoL throughout the trial. Purpose: The purpose of this research is to evaluate the effect of rilonacept on HRQoL in relation to changes in pain for RP patients who have a recurrence. Methods: RHAPSODY enrolled 86 patients with acute symptomatic RP to receive weekly rilonacept for a 12-week run-in (RI) period and randomized 61 patients (1:1) to receive placebo (n=31) or continue rilonacept (n=30) for the event-driven randomized-withdrawal (RW) period. Patients on placebo who experienced a qualifying recurrence during RW (return of pericarditis pain and increase in C-reactive protein) were rescued with bailout rilonacept. Patients reported daily pericarditis pain electronically, using a 0–10 numeric rating scale (NRS), and completed the SF-36v2 at study visits prior to clinician interaction. Scores from RI Baseline (BL), RI Week 12 (RW BL), Recurrence visit, and RW up to Week 24 (or end of study; EOS) were evaluated for patients who experienced recurrence in RW. Analyses exclude one patient randomized to placebo who had a recurrence after Week 24 of the RW period. Results: Analyses focused on the 22 of 30 patients (73%) in the placebo group who experienced a recurrence before Week 24 of RW (median time from RW BL to recurrence: 8.6 weeks). During RI, daily pain scores decreased while on rilonacept (Cohen's effect size [ES] d=−2.0), and SF-36v2 scores improved, with scores at RI BL (Fig. 1 red line) below the general population average of 50 and near or above average at RI Week 12 (Fig. 1 blue line); ES were all large (d>0.8), ranging from 0.917 (Mental Component Summary) to 2.021 (Bodily Pain). At recurrence, pain scores increased (d=6.5; Fig. 2) and SF-36v2 scores were below the population average (Fig. 1 orange line), with largest reductions between RI Week 12 (RW BL) and recurrence for Bodily Pain (−13.4) and Physical Component Summary (−10.6). Following rilonacept bailout, average pain decreased (d=−2.1; Fig. 2), and by RW Week 24/EOS, SF-36v2 scores returned to similar levels as at the end of the RI period (Fig. 1 green line). Conclusion: Impaired RI BL SF-36v2 scores indicate negative impact of RP on HRQOL in RP patients. While receiving rilonacept, HRQoL scores improved to near or above population averages, in conjunction with patient-reported pain. After discontinuing rilonacept during RW, HRQoL scores worsened at recurrence and improved upon receipt of bail-out rilonacept, similar to pain. These results provide support for the broader benefit of rilonacept treatment beyond pain, when administered on top of conventional therapies and as mono-therapy, providing evidence of its potential to improve HRQoL in this patient population. FUNDunding Acknowledgement: Type of funding sources: Other. Main funding source(s): Kiniksa Pharmaceuticals, Ltd.